Analysis of Kyai's Strategy in Cultivating Entrepreneurship among Students (Case Study at Assunniyah, Madinatul Ulum, and Al Bidayah Islamic Boarding Schools) - Miftahul Munir (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2024)
Classic problems frequently faced by Islamic boarding schools include time management strategies, effective business implementation, and limited professional human resources. To address these challenges, Islamic boarding schools have made breakthroughs by cultivating entrepreneurship by providing practical skills to students. It is hoped that these skills will provide important provisions for students when they return to society as alumni. This study used a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Research subjects were determined by purposive sampling, while data validity was tested through source triangulation. The results show that the main strategies of kyai in cultivating entrepreneurship include providing spiritual motivation, a reward system, skills-based training, and providing a place for direct practice. The positive impacts of this cultivation include increased non-religious knowledge, mastery of life skills, mental strengthening, and the formation of entrepreneurial character. However, several obstacles are encountered, such as difficulty identifying students' intentions in participating in the program, limitations in adapting students' interests, challenges in regeneration when students drop out, and difficulties balancing entrepreneurial activities with religious activities. These findings demonstrate the importance of a visionary and adaptive kyai leadership strategy in building an entrepreneurial ecosystem in the Islamic boarding school environment.